Orientation-dependence of incipient plasticity in a coarse-grained Mg revealed by nanoindentation pop-ins - Moein Imani Foumani; Syed Taha Khursheed; Yushun Liu; Guo-zhen Zhu (Journal of Magnesium and Alloys)
The nanoindentation pop-in behaviors of 13 grains with diverse crystallographic orientations were analysed using a coarse-grained Mg-2 wt.% Gd alloy. Within nanoscale stressed volumes within all grains, the converted shear stresses for the first pop-in, calculated using the indentation Schmid factor, ranged from 1 to 1.3 GPa, consistent with theoretical predictions for dislocation nucleation in Mg. The estimated activation volume of the first pop-in was approximately 27–40 Å³ (involving about ∼2 atoms), aligning with reported atomistic simulations of the surface dislocation semi-loop nucleation. While indented near the ⟨c⟩-axis, grains exhibit higher first pop-in loads and successive pop-ins, implying the possibility of a cross-slip nucleation mechanism to accommodate ⟨c⟩-axis deformation.